WORKSHOP PELATIHAN PENULISAN PUISI SEBAGAI PERWUJUDAN TRI DHARMA PERGURUAN TINGGI: Poetry Writing Training Workshop As An Embodiment Of The Tri Dharma Of Higher Education - Putra, Sandi Justitia; Audina, Pin Kharisma; Mandini, Denda Devi Sarah; Husbuyanti, Irma El-Mira; Ningrum, Anisa Purwa; Rahmat, Lalu Ahmad; Rahmandari, Ismi Arifiana; Sumanjayadi, Sumanjayadi; Hambali, MS; Arisandy, Rita; Sarlan, Yani Rosita; Zulhadi, Zulhadi; Kahfi, Rido Ashabul (Yayasan Al-Amin Qalbu, 2025)
The Poetry Writing Training Workshop in North Lombok Regency aims to improve writing skills, literary appreciation, and strengthen local cultural identity. This activity produced 50 original poems compiled in an anthology. The positive impacts were seen in the increasing interest of participants in writing, awareness of cultural preservation, and the formation of an active literacy community. This article reviews the methodology, results, and implications of the workshop for the development of local literature and culture. It is hoped that similar activities can strengthen the literacy ecosystem and build awareness of the younger generation towards the importance of cultural expression through literature.